THE PURPOSE OF EDUCATION AND ITS MEANING IN ACCORDANCE WITH ISLAM'S TEACHINGS - Paiman; Kosim; Kadar Risman; Nur Faiz Habibah; Mohammad Ahmad Bani Amer (International Journal of Teaching and Learning, 2024)
This research is aimed at finding out the purpose of Islamic education contained in the Qur'an. The research method used is the maudu’i tafsir method, with a descriptive qualitative approach and type of library study research. Thus, the prophet Muhammad (peace be upon him) said: “The prophecy of Allah is that the people of the world and of the Hereafter should be worshippers of all things. The Qur'an repeats many verses about those who are given knowledge with faith and worship. He who has knowledge and faith gives birth to a man who fears him, and he will be exalted in the rank of his Lord.